Adolescence and drug use vulnerability: findings from neuroimaging. (February 2017) - Squeglia, Lindsay M; Cservenka, Anita
Highlights: Adolescence is a period of vulnerability for developing substance use disorder. Executive functioning deficits are predictive of substance use initiation. Reduced brain volume and response are present before initiating substance use. Youth with familial substance use disorder have altered brain structure/activity. These findings may aid prevention studies aimed at reducing youth substance use. Abstract : Adolescence is a period of vulnerability for developing substance use disorder. Recent neuropsychological and neuroimaging studies have elucidated underlying neural vulnerabilities that contribute to initiation of substance use during adolescence. Findings suggest poorer performance on tasks of inhibition and working memory, smaller brain volumes in reward and cognitive control regions, less brain activation during executive functioning tasks, and heightened reward responsivity are predictive of youth initiating substance use during adolescence. In youth who are family history positive (FHP) for substance use disorder, poorer executive functioning, smaller volume of limbic brain regions (e.g., amygdala), sex-specific patterns of hippocampal volume, and a positive association between nucleus accumbens volume and family history density have been reported. Further, reduced white matter integrity, altered brain response during inhibitory control, including both greater and less frontal lobe response, blunted emotional processing, and weaker neural connectivity have also been found in FHP youth. Thus, there is significant overlap among the neural precursors shown to be predictive of alcohol and substance use initiation during adolescence and those that distinguish FHP from youth without a family history of substance use disorder, suggesting common targets for prevention and intervention. Understanding these predictive factors helps identify at-risk youth for prevention efforts, as well as create interventions targeting cognitive weaknesses or brain regions involved in substance use initiation.